Investigating the Relationship between Fear of Failure and the Delivery of End-of-Life Care: A Questionnaire Study - John S. Latham; Hannah Sawyer; Sarah Butchard; Stephen R. Mason; Kathryn Sartain (MDPI AG, 2023)
Objective: To investigate whether fear of failure (FOF) influences a clinician's perception of how confident and comfortable they are in their delivery of end-of-life (EOL) care. Methods: Cross-sectional questionnaire study with recruitment of physicians and nurses across two large NHS hospital trusts in the UK and national UK professional networks. A total of 104 physicians and 101 specialist nurses across 20 hospital specialities provided data that were analysed using a two-step hierarchical regression. Results: The study validated the PFAI measure for use in medical contexts. Number of EOL conversations, gender, and role were shown to impact confidence and comfortableness with EOL care. Four FOF subscales did show a significant relationship with perceived delivery of EOL care. Conclusion: Aspects of FOF can be shown to negatively impact the clinician experience of delivering EOL care. Clinical Implications: Further study should explore how FOF develops, populations that are more susceptible, sustaining factors, and its impact on clinical care. Techniques developed to manage FOF in other populations can now be investigated in a medical population.